Glial cell line-derived neurotrophic factor in patients with age-related cataract - A.A. Shpak; A.B. Guekht; T.A. Druzhkova; A.A. Troshina; N.V. Gulyaeva (Офтальмохирургия)
Purpose. To study the content of glial cell line-derived neurotrophic factor (GDNF) in the aqueous humor (AH), lacrimal fluid (LF), and blood serum (BS) in patients with age-related cataract. Material and methods. The content of GDNF in the LF, AH and BS was studied in 47 patients (47 eyes) with age-related cataract. Collection of stimulated LF was performed with a pipette on the day preceding surgery; the AH and BS were sampled during the phacoemulsification of a cataract. The concentration of GDNF was measured using an enzyme immunoassay. Results. The concentration of GDNF in the AH was 88.9±46.9 (2.0–212.5) pg/ml, in the BS – 201.1±44.6 (103.2–287.2) pg/ml, in the LF – 343.6±133.7 (172.8–683.0) pg/ml. The levels of GDNF in the studied biological fluids did not show any significant correlations with each other. Conclusion. In patients with age-related cataract, the level of GDNF in the AH was relatively low: the concentration of GDNF in the AH was more than 2 times lower than in the BS and almost 4 times lower than in the LF. No significant correlations were found between the concentrations of GDNF in LF, AH and BS.